A LEITURA LITERÁRIA NA EDUCAÇÃO INFANTIL: ANÁLISE DE NARRATIVAS ESCRITAS POR UMA PROFESSORA - Martins, Ana Carolina Ferreri; Bortolanza, Ana Maria Esteves (Revista Ciranda, 2021)
The aim of the article is to analyze theoretical and practical aspects of literary reading in Early Childhood Education through written narratives by a teacher. The study (2019-2020) was elaborated by means of a qualitative research of exploratory character, having as procedure two narratives written by a teacher of a class of 5 years, in a school of Infantile Education of Tubarão, SC. It explores practical and theoretical questions about literary reading in children’s activities with the objects of writing, specifically, children’s literature books. The article highlights the distance between the theoretical aspects of literary reading in relation to the pedagogical practices of the teacher participating in the research. We conclude that it is necessary, in Early Childhood Education, to organize the conditions for the child’s experience with literary reading as a space for sharing and relationships that enable children’s interactions with literary reading in daily life.